A set of novel multiplex Taqman real-time PCRs for the detection of diarrhoeagenic Escherichia coli and its use in determining the prevalence of EPEC and EAEC in a university hospital - Würthner Jens; Pfeffer Klaus; Henrich Birgit; Messler Sabine; Hardegen Christoph; MacKenzie Colin R (BMC, 2010)
Abstract Background Accurate measurement of the incidence of diarrhoeagenic E. coli in patients with diarrhoea is hindered by the current methods of detection and varies from country to country. In order to improve the diagnosis of diarrhoeagenic E. coli (DEC), we developed a set of multiplex TaqMan real-time PCRs designed to detect the respective pathogens from an overnight stool culture. Methods Over the period Jan. 2006 to Dec. 2006 all stool specimens (n = 1981) received were investigated for EPEC and EAEC. Results Of these, 371 specimens had no growth of Enterobacteriaceae. Of the remaining 1610 specimens 144 (8,9%) were positive for EPEC and 78 (4,8%) positive for EAEC. Among the EPEC positive stool specimens 28 (19,4%) were received from the tropical diseases unit, 49 (34%) from the paediatric dept. and 67 (46,5%) from the remainder of the wards. The EAEC were distributed as follows: 39 (50%) - tropical diseases, 19 (24,4%) -paediatrics and 20 (25,6%) other wards. Proportionately more EAEC and EPEC were found in children less than 3 years of age than other age groups. In only 22,2% of the detected EPEC and 23% of EAEC was the investigation requested by hospital staff. Conclusions This is, to our knowledge, the first study using a multiplex TaqMan PCR for the successful detection of diarrhoeagenic E. coli. In conclusion, due to the high prevalence of DEC detected, investigation of EPEC and EAEC should be recommended as a routine diagnostic test for patients with infectious diarrhoea.